Relationship between Energy Intake and Obesity Prevalence among Adolescent Girls in Aceh Barat - Afwa Hayuningtyas; Wardah Iskandar; Suci Eka Putri; Safrida Safrida; Adelina Irmayani Lubis (Journal of Nutrition Science, 2021)
The prevalence of adolescent obesity has been shown to differ among regions, and it could be influenced by several factors including diet, environmental exposures, and lifestyle. Diet is one of crucial factors that contribute to obesity among adolescents, particularly energy intake. This study was conducted to measure the relationship between energy intake and obesity prevalence among adolescent girls in Aceh Barat Regency. This study is a descriptive analytical research with the design of cross-sectional study. The population in this study were adolescent girls in Aceh Barat Regency with the samples of 50 people. The data were obtained from a one day 24-hour recall and analyzed using Chi-Square test with a significance value (p= 0.05). The result showed that based on bivariate analysis there is a relationship between energy intake and body mass index. The analysis indicated that adolescent girls with excessive energy intake had a 6.67-fold higher risk of obesity than those with the adequate energy intake (OR: 6.67, 95% CI: 1.25-35.65).